Digital transformation of industrial enterprises: trends and strategies - T. A. Gileva (Модернизация, инновация, развитие)
Purpose: is to form the methodological approach to the development of the strategy for the digital transformation of an industrial enterprise, taking into account current industry trends.   Methods: the research used methods of analysis and synthesis, a systematic approach, methods of bibliometric, statistical and content analysis of literary sources. The source of information was the Scopus and eLibrary databases. The depth of the study covers the period 2022–2023. To consider individual analytical sections, the depth of the study increased until the 1980s.   Results: in terms of identifying trends and factors of successful digital transformation, the methods of systematic review of relevant scientific publications, results of empirical studies and analytical reports, as well as the analysis of statistical data were used. The justification of decisions in the field of developing the digital strategy of an industrial enterprise is based on approaches to the identification of strategic archetypes, concepts in the field of increasing the flexibility of the strategies and the method of matrix structuring.   Conclusions and Relevance: based on the conjugation of the features of the identified strategic archetypes with the conditions of their effective application and the trends of digital transformation of Russian industry, the model for the formation of the digital strategy of an industrial enterprise «digital crossroads» was developed. The peculiarity of the proposed model, which provides increased flexibility of the strategy, is the situational nature of recommendations depending on the chosen direction of development (in terms of products and markets), taking into account the pace of digital transformation of the industry (market) and the level of digital maturity of the enterprise. The specific list of strategic actions, as well as the possibility of supplementing them, will ensure the full implementation of the preferred strategic alternative in a continuously changing digital environment.